Epidemiology of cytomegalovirus Infection among mothers and infants in Colombia. Issue 11 (1st February 2021) - Rico, Angelica; Dollard, Sheila C.; Valencia, Diana; Corchuelo, Sheryll; Tong, Van T.; Laiton‐Donato, Katherine; Amin, Minal M.; Benavides, Monica; Wong, Phili; Newton, Suzanne; Daza, Marcela; Cates, Jordan; et al.
Abstract: We assessed maternal and infant cytomegalovirus (CMV) infection in Colombia. Maternal serum was tested for CMV immunoglobulin G antibodies at a median of 10 (interquartile range: 8–12) weeks gestation ( n  = 1501). CMV DNA polymerase chain reaction was performed on infant urine to diagnose congenital (≤21 days of life) and postnatal (>21 days) infection. Maternal CMV seroprevalence was 98.1% (95% confidence interval [CI]: 97.5%–98.8%). Congenital CMV prevalence was 8.4 (95% CI: 3.9%–18.3%; 6/711) per 1000 live births. Among 472 infants without confirmed congenital CMV infection subsequently tested at age 6 months, 258 (54.7%, 95% CI: 50.2%–59.1%) had postnatal infection. Highlights: In this multi‐city study in Colombia, maternal CMV seroprevalence was 98.1%, the prevalence of congenital CMV infection was 8.4 per 1000 live births, and 54.7% of infants had postnatal infection by 6 months of age.